2008
DOI: 10.1111/j.1540-8159.2008.01147.x
|View full text |Cite
|
Sign up to set email alerts
|

Discriminatory Therapy for Very Fast Ventricular Tachycardia in Patients with Implantable Cardioverter Defibrillators

Abstract: This study has demonstrated for the first time that ATP and low-energy shock are effective, as an alternative to high-energy shock, to revert induced VFVT. Low-energy shock has a very high success rate for VT slower than VFVT. Clinical studies are required prior to consideration for empiric programming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
2
19
0
Order By: Relevance
“…This programming might improve survival [126]. Indeed, several studies have shown that ATP is effective at terminating slow and fast VT with exceedingly low rates of adverse events like syncope [93,135,[161][162][163][164][165]. The initial bias of the ICD community was to reserve ATP therapy for those patients in whom the therapy was demonstrated to be effective, usually during an electrophysiologic study.…”
Section: Tachycardia Therapy Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…This programming might improve survival [126]. Indeed, several studies have shown that ATP is effective at terminating slow and fast VT with exceedingly low rates of adverse events like syncope [93,135,[161][162][163][164][165]. The initial bias of the ICD community was to reserve ATP therapy for those patients in whom the therapy was demonstrated to be effective, usually during an electrophysiologic study.…”
Section: Tachycardia Therapy Programmingmentioning
confidence: 99%
“…It is not reflective of the arrhythmias experienced outside the electrophysiology laboratory for primary and secondary prevention patients with ischemic and nonischemic substrates [101,166]. Although the ideal number of ATP bursts has not been definitively determined, current data support the use of up to 2 ATP attempts, given additional attempts yield very little additional efficacy [93,135,[161][162][163][164][165]167,168]. In one study, up to 5 attempts were found to be safe [168].…”
Section: Tachycardia Therapy Programmingmentioning
confidence: 99%
“…3 For inducible VFVT, the pilot study demonstrated a success rate of 30% for ATP and 86% for LES. 2 We postulated that the success rate would be higher for spontaneous VT. Assuming at least 80% respond to the combination ATP AE LES, then the 95% confidence interval for the estimated response rate among the 24 subjects with VFVT would be no wider than AE16% about the estimated response rate.…”
Section: Methodsmentioning
confidence: 99%
“…1 Previously, we have demonstrated that antitachycardia pacing (ATP) and low-energy shock (LES) can be used for very fast ventricular tachycardia (VFVT) CL of <250 ms in the setting of induced ventricular tachycardia (VT) at the time of implantable cardioverter-defibrillator (ICD) implant. 2 However, traditional ICD programming for VFVT remains to be high-energy shock (HES). This study examined the effectiveness of ATP for VT CL of 200 to 250 ms and the use of LES when ATP fails for VT of any CL.…”
mentioning
confidence: 99%
“…10 Programming that delays ICD therapy in primary prevention patients with therapy of more than 200 beats per minute or more than 170 beats per minute after a prolonged detection has been shown to decrease inappropriate shocks and may even be associated with improved mortality. 11 There is growing evidence that antitachycardia pacing (ATP) is effective for treating fast VT. [12][13][14][15][16][17] All of these findings have resulted in the goal of reducing inappropriate and appropriate ICD shocks with optimal device programming, such as with turning on ATP for fast VT.…”
Section: Introductionmentioning
confidence: 99%